Financial cryptography and data security : 17th International Conference, FC 2013, Okinawa, Japan, April 1-5, 2013, Revised Selected Papers - Sadeghi, Ahmad-Reza (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 17th International Conference on Financial Cryptography and Data Security (FC 2013), held at Bankoku Shinryokan Busena Terrace Beach Resort, Okinawa, Japan, April 1-5, 2013. The 14 revised full papers and 17 short papers were carefully selected and reviewed from 125 submissions. The papers are grouped in the following topical sections: electronic payment (Bitcoin), usability aspects, secure computation, passwords, privacy primitives and non-repudiation, anonymity, hardware security, secure computation and secret sharing, authentication attacks and countermeasures, privacy of data and communication, and private data retrieval.